Understanding Buddhism - Buckey, A. W. (Understanding world religions and beliefs., 2019)
Describes the traditions, history, core beliefs, practices, and challenges of Buddhism. Also discusses the future of the religion. Includes a facts section, color photographs, a glossary, and further resources.